Current and potential providers of blood pressure self-screening: a mixed methods study in Oxfordshire. Issue 3 (22nd March 2017) - Tompson, A C; Fleming, S G; Heneghan, C J; McManus, R J; Greenfield, S M; Hobbs, F D R; Ward, A M
Abstract : Objectives: To (1) establish the extent of opportunities for members of the public to check their own blood pressure (BP) outside of healthcare consultations (BP self-screening), (2) investigate the reasons for and against hosting such a service and (3) ascertain how BP self-screening data are used in primary care. Design: A mixed methods, cross-sectional study. Setting: Primary care and community locations in Oxfordshire, UK. Participants: 325 sites were surveyed to identify where and in what form BP self-screening services were available. 23 semistructured interviews were then completed with current and potential hosts of BP self-screening services. Results: 18/82 (22%) general practices offered BP self-screening and 68/110 (62%) pharmacies offered professional-led BP screening. There was no evidence of permanent BP self-screening activities in other community settings. Healthcare professionals, managers, community workers and leaders were interviewed. Those in primary care generally felt that practice-based BP self-screening was a beneficial activity that increased the attainment of performance targets although there was variation in its perceived usefulness for patient care. The pharmacists interviewed provided BP checking as a service to the community but were unable to develop self-screening services without a clear business plan. Among potential hosts, barriers to providing a BP self-screening service included a perceived lack of healthcare commissioner and public demand, and a weak—if any—link to their core objectives as an organisation. Conclusions: BP self-screening currently occurs in a minority of general practices. Any future development of community BP self-screening programmes will require (1) public promotion and (2) careful consideration of how best to support—and reward—the community hosts who currently perceive little if any benefit.